PENGARUH MANAJEMEN LABA, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERDAGANGAN JASA & INVESTASI SEKTOR PERDAGANGAN BESAR BARANG PRODUKSI YANG TERDAFTAR DI BEI - Rahadi, Akbar Pulung; Ediyanto, Ediyanto; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
Produce other products. This study aims to determine the Influence of Profit Management, Capital Structure, and Company Size on Company Value with Profitability as an Intervening Variable in Trading, Services and Investment Companies in the Large Trade Sector of Production Goods Listed on the IDX. This research method uses a quantitative method. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that profit management has a significant positive effect on profitability, Capital structure has a positive effect on profitability, Company size has a positive but not significant effect on profitability, Profit management has a significant negative effect on company value, Capital structure has a significant negative effect on company value, Company size has an effect negative but not significant to company value, Profitability has a positive but insignificant effect on company value. Profit management has a positive but insignificant effect on company value through Profitability, Capital structure has a positive but insignificant effect on company value through Profitability, Company size has a positive but insignificant effect on company value through Profitability.